1991
DOI: 10.1073/pnas.88.24.11158
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of focal cerebral ischemic injury in transgenic mice overexpressing CuZn superoxide dismutase.

Abstract: Oxygen-derived free radicals have been implicated in the pathogenesis of vasogenic edema and infarction caused by ischeria and reperfusion injury. In earlier studies, exogenously supplied liposome-entrapped CuZn superoxide dismutase (CuZn-SOD) ameliorated ischemic brain edema and infarction in rats following focal cerebral ischemla. To ascertain directly the role of SOD in the protection against superoxide radical-induced injury, we measured infarct size and water content 24 hr following focal cerebral ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
244
1
4

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(256 citation statements)
references
References 40 publications
7
244
1
4
Order By: Relevance
“…Therefore, antioxidant enzymes controlling ROS production possess the ability to effectively modulate the development of brain injury during I/R. Indeed, as shown by us and others, transgenic mice overexpressing antioxidant enzymes demonstrate significant protection, whereas knockout animals with reduced antioxidant defense show increased sensitivity to brain I/R injury (5,27,28). To investigate possible mechanisms of protection demonstrated by GPx1, we analyzed the inflammatory response in normal and transgenic mice after I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, antioxidant enzymes controlling ROS production possess the ability to effectively modulate the development of brain injury during I/R. Indeed, as shown by us and others, transgenic mice overexpressing antioxidant enzymes demonstrate significant protection, whereas knockout animals with reduced antioxidant defense show increased sensitivity to brain I/R injury (5,27,28). To investigate possible mechanisms of protection demonstrated by GPx1, we analyzed the inflammatory response in normal and transgenic mice after I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect strategies to study the role of ROS for ischemic damage have used compounds that inter act with ROS production (particularly ROS scaven gers; for overview see Traystman et al , 1991), and more recently transgenic approaches were used [i. e. , Cu-Zn-SOD overexpressing mice (Kinouchi et al , 1991;Halliwell et al , 1992)]. With very few exceptions, these studies have shown in a number of different ischemia models and species that exper imentally induced increases in the capacity of the brain to cope with oxidative stress are neuroprotec tive.…”
Section: Short Periods Of Hypoxia (Inhalation Of 100% N2)mentioning
confidence: 99%
“…36 It is significant that focal cerebral ischemic injury is attenuated in transgenic mice constitutively overexpressing superoxide dismutase. 115 The complex relation between ROS-induced events and anoxia is illustrated by the finding that morphological damage to the penumbra region around an ischemic region is generally more severe than at the core. 107 The presence of excess oxygen free radicals in post-ischemic tissue has been directly demonstrated.…”
Section: Stroke and Ischemiamentioning
confidence: 99%